2008
DOI: 10.1007/s12291-008-0022-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E on protein bound carbhohydrate complexes in radiation treated oral squamous cell carcinoma patients

Abstract: Serum glycoproteins were evaluated in oral squamous cell carcinoma patients treated with radiotherapy and also the effect of vitamin E was studied. Cell surface glycoconjugates are important parameters in the detection of malignancy. Thus, the objective of the present study is to evaluate the efficacy of vitamin E on glycoproteins in oral cavity cancer patients treated with radiotherapy. The study includes 26 age and sex matched normal healthy individuals and 26 patients with squamous cell carcinoma of oral ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In this study we observed significantly higher serum levels of sialic acid in OSMF, Leukoplakia and OC ( P < 0.01) and were positively correlated with findings of other studies. [3032] Neoplasms often have increased concentration of sialic acid on tumor cell surface and sialoglycoproteins are shed or secreted by these cells increasing their concentration in blood. This increase in cancer is might also be due to selective increase in existing specific sialylated sequence or a tumor associated de-nova synthesis of specific sialylated sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we observed significantly higher serum levels of sialic acid in OSMF, Leukoplakia and OC ( P < 0.01) and were positively correlated with findings of other studies. [3032] Neoplasms often have increased concentration of sialic acid on tumor cell surface and sialoglycoproteins are shed or secreted by these cells increasing their concentration in blood. This increase in cancer is might also be due to selective increase in existing specific sialylated sequence or a tumor associated de-nova synthesis of specific sialylated sequence.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Serum fucose is considered a better biochemical marker than sialic acid level in oral squamous cell carcinoma. [31,39] Some studies have concluded that it is most effective of the essential sugars when it comes to slowing the growth of cancer cells. [3,4] Decrease in serum fucose levels after treatment has been observed by different workers, although it is emphasized that follow-up period has to be long enough.…”
Section: Discussionmentioning
confidence: 99%
“…Serum fucose level is considered a better biochemical tumor marker than sialic acid level in oral squamous cell carcinoma. [ 28 29 ] Some studies have concluded that fucose and mannose appeared to be the most effective of the essential sugars when it came to slowing the growth of cancer cells. [ 4 5 ] Although, mean serum fucose levels after therapy was found to be decreased, some of the follow-up cases showed an elevation after radiation and chemotherapy in the present study.…”
Section: Discussionmentioning
confidence: 99%